Liderazgo y reconstrucción del Estado en el Posconflicto: Irak después del 2003 (2020)
The Iraqi political and social arena has been characterized, subjectively and objectively, by the weakness of leadership building. This has led to a leadership crisis, reflected in the quality of the outcome of the process of rebuilding the state in Iraq. Thus, this building process lacked the simplest requirements and conditions of success. It suffered from a major and obvious failure: the situation in Iraq has raised conflict leaders, not building leaders, and this confirms the existence of a cultural crisis in the production of conscious, aware leadership compatible with democratic action. The weakness of the leadership in Iraq is reflected in a series of ongoing crises that require radical solutions in accordance with long-term strategic plans; the crises are especially reflected in the absence of building visions and the predominance of self-interest, along with the impact of social reality on leadership practices, which has an adverse effect on state-building.